Formal and material effectiveness of the performative - Łukowski, Łukasz (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
Effectiveness of the performative is usually understood as fulfillment of all the conditions ensuring its proper presentation. This approach is justified on the logical and philosophical basis. On the basis of jurisprudence it seems to be equally important to consider another kind of performative effectiveness which is granted irrespectively of the fact that the performative actually leads to predicate its reality changes. The first type of the effectiveness distinguished by Searle is called in this work formal effectiveness while the second type – material. Combinatorial connection of achieving or not these two kinds of effectiveness gives four cases. In a democratic state there are cases that meet the desired material performatives, which are also met formally, and non-compliance of the material performatives, which are also not formally met. Other configurations to meet performatives are undesirable. As the analysis of specific cases of performatives in the matter of law (legal norms) shows, this regularity does not occur when the functioning of democracy suffers. This fact implies a possibility of „performative” definition of a democratic system, understood as the rule of law.